Supply Chain Management in the Building Construction Industry: Linking Procurement Process Coordination, Market Orientation and Performance - Othman, Akmal Aini; Abd Rahman, Sofiah (Journal of Surveying, Construction and Property, 2010)
Supply chain (SC) is basically a network of firms involved in complex activities and multi processes. With such complexities, this management of interdependencies require to be coordinated to improve the performance of SC i.e. on flow of information, services, money and material. Various areas of supply chain management (SCM) have been explored by the researchers including supply chain coordination (SCC) and managing supplier relations. The initial part of this paper presents a conceptual discussion and framework of the link between market orientation, procurement process coordination and performance in the construction industry. It is supported with the result from a pilot case study in the building construction sector. The discussion from the pilot case study concentrates on the importance of market orientation and each activity in the procurement process coordination. Finding from this study illustrates that the importance of procurement process coordination in the construction industry slightly varies from manufacturing. While, several means of coordination could be adopted, information sharing and supply contract were demonstrated to be visible. Keywords: Supply Chain Management, Market orientation, Procurement, performance & construction